Evaluasi Program Pendidikan Inklusif dengan Menggunakan CIPP Model - Khasyia, Dhaifa Shafya; Ramdhani, Muh Fikri Akbar; Qodari, Muzzamil Ali; Dhafiana, Nabila; Azzahra, Naila; Zanah, Nok Nessa Raudatul; Yustiyati, Sylvia; Lailapuspa, Hilma; Lestari, Triana (Afkaruna: International Journal of Islamic Studies (AIJIS), 2024)
The inclusive education program aims to integrate children with special needs (ABK) and children without special needs into the same classroom to foster social interaction and appropriate learning experiences. SD Laboratorium UPI Cibiru is one of the schools implementing this program, although it faces challenges such as limited facilities, insufficient teacher training, and a lack of coordination among stakeholders. This study aims to evaluate the implementation of the inclusive education program at SD Labschool UPI using the CIPP (Context, Input, Process, Product) evaluation model developed by Daniel Stufflebeam. This research is an evaluative study with a qualitative approach. Data collection techniques include observation, interviews, and questionnaires. The results show that in the Context component, policies and support for the program are adequate, although increased awareness among all parties is needed. In the Input component, the curriculum has been adapted for inclusive needs, but teacher training and supporting facilities, especially classrooms for ABK, require further improvement. In the Process component, teaching is conducted using differentiated methods such as interactive lectures and individual or group assignments; however, the implementation has not yet been optimal. In the Product component, the program demonstrates significant positive impacts on the academic and social development of ABK. This study emphasizes the importance of continuous improvement in program implementation to enhance the effectiveness of inclusive education in the future.